Siyāq Numbers on Copper Coins and Countermarks during the Qajar Era - Mohammadi, Seyed Omid (JAOS, 2024)
Iranian copper coins of the Qajar era—all described by the word falus—have a great variety of designs, weights, and sizes. These coins sometimes also include letters and phrases that are undeciphered to date. This article uses siyāq script to read some of these mystery notations for the first time. The multiple fascinating examples of siyāq numbers found thereby on Qajar coins and countermarks show that, contrary to former belief, some copper coins of this era had specific face values written on them in the siyāq script. This research uses these copper coins to take a small step toward a better understanding of the monetary system of the Qajar era by introducing several denominations never reported before. Finally, as siyāq script had never been discovered on coins, this new possibility now allows numismatists and scholars to revisit and correct former interpretations or to intro- duce and decipher new coins in the future.